Job Crafting as an Adaptive Strategy to Prevent Burnout in Digital Work Enviroments - P, Muhammad Carda; Basalamah, Indira (SAFE-Network, 2025)
This study examines the role of job crafting as an adaptive strategy to prevent burnout in digital work environments where employees face continuous connectivity, rapid communication cycles, and high task intensity. The objective of this research is to identify how different forms of job crafting contribute to reducing emotional exhaustion and sustaining employee well being in technology driven settings. A quantitative descriptive design was used, supported by an online survey distributed to employees working in digital or hybrid arrangements across various sectors. The data collected included job crafting behaviors, burnout indicators, and perceived digital work demands. The analysis revealed that job crafting shows a significant negative relationship with burnout, indicating that employees who proactively modify their tasks, interactions, and perceptions tend to experience lower levels of strain. Task crafting demonstrated the strongest effect in reducing burnout, while relational and cognitive crafting also contributed meaningful support. Digital work demands, on the other hand, were found to have a strong positive influence on burnout, highlighting the pressure created by constant digital engagement. The findings conclude that job crafting functions as a practical, flexible, and effective strategy for enhancing resilience and maintaining psychological balance in digital workplaces. The study provides empirical insights that can guide organizations in designing healthier and more adaptive digital work systems.